Room Renting Management System - Iu, Chin Shee; Mohd Zaki Mohd Salikon (Applied Information Technology And Computer Science, 2022)
This study aimed to discuss the development of an online management system for the Room Renting Management System. The advantage is to enable the business owner to view the total rental and the new payment received in line graph. The business owner is also able to view the total bill of the owner and tenant through the month. In this system, the waterfall model is used for the whole system. It involves six processes: requirement analysis, system design, implementation, system testing, system deployment, and system maintenance. Throughout the development process, this system takes an object-oriented approach and uses visual modelling extensively. Rapid PHP 2020 was used to develop the programming code, while HeidiSQL was used to store the data. This system design should ensure that the system is completely functioning, user-friendly, and completed within the specified time frame. The development of this system will encourage the admin to view all the details just right on the dashboard, and the significance for the user can make payment directly from the system. By the end of the project, a new room renting management system has been developed and ensures every function can be used correctly without an error